Experimental study of the mechanical properties and microstructure of geopolymer paste containing nano-silica from agricultural waste and crystalline admixtures - Ar Razi Alvee (Elsevier, 2022)
This study explored the influence of nano-silica and Crystalline Admixture (CAs) on the mechanical properties and microstructure of geopolymer pastes. Nano-silica and CAs was added to the mixture at 3%, 4% and 5% respectively by weight of fly ash. The bulk density, the yield stress of geopolymer paste, compressive strength, and flexural bending tests were carried out to evaluate the effect of nano-silica and CAs effect on the geopolymer paste. Scanning Electron Microscopy (SEM), X-ray Diffraction (XRD), Transmission Electron Microscope (TEM), and Fourier Transform Infrared Spectroscopy (FTIR) techniques are employed to examine the microstructure of nano-silica and geopolymerization products. The test results demonstrated that adding nano-silica and CAs by 5% increased the bulk density by 5.32%, yield stress by 64.20%, compressive strength by 33.63%, flexural strength and fracture toughness by 232.69% than the control specimens, respectively. The SEM, XRD, and FTIR analysis revealed that the effect of nano-silica and CAs on geopolymer paste occurred mainly in increasing the CSH bond and self-healing products. These findings suggest that rice husk ash can be processed into nano-silica by the sol-gel method and combined with CAs to obtain better mechanical strength.